Do Suburban Populations of Lizards Behave Differently from Forest Ones? An Analysis of Perch Height, Time Budget, and Display Rate in the Cuban Endemic Anolis homolechis - Annabelle Vidal; Roger Pradel; Frank Cézilly (Diversity, 2023)
Urbanization transforms natural ecosystems into novel habitats, which can result in negative consequences for biodiversity. Therefore, it is important to understand the mechanisms of maintenance of native species in urbanized environments, including behavior—which can act as a fast response to rapid environmental changes. We compared some behavioral traits between two suburban and two forest populations of Anolis homolechis. Direct observations of 779 individuals revealed that perch height was positively influenced by body size, but not by sex. Suburban individuals perched higher than forest ones, and even more so in the afternoon compared to the morning; a behavior that was not observed in forests populations. These differences might be due to a change from foraging activities in the morning to vigilance, display, and/or thermoregulation in the afternoon, promoted by suburban habitat conditions (e.g., higher predator abundance, open habitat structure, and urban heat). Video recordings of 81 focal individuals showed that males were more active than females (i.e., spending less time in stationary behavior and having a higher display rate), with no significant effect of habitat type. As some of our results diverge from previous studies on invasive anoles, we recommend extending comparative studies of urban and non-urban populations to other native Anolis.